Real-world landscape of drug-related ocular injuries: a retrospective pharmacovigilance study - Li, Guangyao; Song, Zhihui; Li, Shuning; Wang, Jiawei (Frontiers in Pharmacology, 2026)
ObjectiveThis study aimed to detect risk signals of drug-related ocular injuries, delineate their real-world epidemiological features, and provide evidence-based guidance for safe clinical use by utilizing the US Food and Drug Administration Adverse Event Reporting System (FAERS).MethodsAdverse event reports classified under “Eye disorders” (System Organ Class, SOC) were extracted from the FAERS database covering Q1 2004 to Q4 2024. Disproportionality analyses were employed to identify drug-ocular injury associations, and the time-to-onset (TTO) of adverse reactions was analyzed using Weibull distribution modeling.ResultsA total of 1,242,518 reports from 832,314 patients were included, with females accounting for 60.56% and elderly patients (≥65 years) for 21.63%. Serious outcomes comprised 62.80% of the reports. In total, 2,696 primary suspect drugs were identified, of which 359 met the signal detection criteria. High-risk drug categories included sensory organ drugs (ATC: S class, ROR = 4.93) and antineoplastic/immunomodulating agents (ATC: L class, most reports but ROR = 0.84). The top three drugs by signal strength were brolucizumab (ROR = 132.15), macrogol 400 (ROR = 117.96), and cenegermin (ROR = 60.19). The most common ocular injury types were blurred vision (121,517 cases), visual impairment (113,320 cases), and cataract (51,826 cases). TTO analysis indicated that most drugs exhibited an “early failure type” (β < 1), such as dupilumab (β = 0.68); only two drugs exhibited a random failure type.ConclusionThe risk of drug-related ocular injuries is primarily associated with sensory organ drugs and biologics, with the greatest risk occurring during the early treatment phase. Clinical monitoring should prioritize female and elderly patients, especially regarding ocular symptoms at the onset of drug therapy, to strengthen pharmacovigilance and inform personalized medication.